Financial Literacy and Cryptocurrency Investment Decision-Making: A Qualitative Study of University Students in Makassar - Amin, Andi Mustika (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This qualitative study explores the relationship between financial literacy and cryptocurrency investment decision-making among university students in Makassar, Indonesia. Using interpretive phenomenological analysis, 23 semi-structured interviews were conducted across three major universities to understand how students navigate the intersection of traditional financial knowledge and digital asset investments. The findings reveal four distinct decision-making pathways: impulse-driven decisions influenced by social media, peer-influenced investments, analytical approaches, and cautious observation. Despite 74% of participants demonstrating basic traditional financial literacy, only 35% possessed comprehensive financial planning knowledge, while 83% could articulate blockchain concepts but lacked sophisticated risk assessment skills. Social networks, particularly family attitudes and peer influence, emerged as dominant factors shaping investment behaviors, with 65% learning about cryptocurrencies through peer recommendations. The study reveals that initial investment decisions typically occurred within 24-48 hours of first exposure, driven by fear of missing out (FOMO). These findings suggest that effective financial education must address social influences and emotional factors beyond traditional financial knowledge to support informed cryptocurrency investment decisions among young investors.